Trapping Power of Incandescent Light Color Traps against Copra Pests in Minahasa Regency - Tarore, Dantje; Manueke, Jusuf; Montong, Vivi B.; Paat, Frangky J.; Mandey, Lucia Cecilia; Kandowangko, Daisy S. (Jurnal Agroekoteknologi Terapan, 2025)
This study aims to determine the trapping efficacy of white, red, blue, green, and yellow incandescent light color traps on copra pest populations. The study employed a completely randomized design (CRD) with five treatments and three replications. The treatments were as follows: A = white light trap, B = red light trap, C = blue light trap, D = yellow light trap, E = green light trap, and F = control (trap without light). This research uses a descriptive exploratory approach. The results indicated that three types of copra pests were trapped across the five light color traps: Necrobia rufipes, Carpophilus dimidiatus, and Tribolium castaneum. N. rufipes had the highest number of trapped adults, averaging 194.32 individuals, followed by C. dimidiatus with 112.0 individuals, while T. castaneum had the lowest count with 99.66 individuals. The highest populations of trapped N. rufipes, C. dimidiatus, and T. castaneum were observed in the white (42.0 adults), red (26.33 adults), and yellow (21.33 adults) incandescent light traps, respectively. Keywords: Catching power test, light traps, copra insect pests, pests control.